Penyelesaian Overcrowded Sebagai Bentuk Implementasi Convention Against Torture Guna Mewujudkan Stabilitas Keamanan Lembaga Pemasyarakatan dan Rumah Tahanan Negara di Indonesia - Heru Yoga Pamungkas; Adnan Madjid; Irwan Triadi; Pujo Widodo; Achmed Sukendro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research addressed the resolution of overcrowding as a form of implementing the Convention Against Torture to achieve security stability in prisons and detention centers in Indonesia. Errors in the calculation of prisoner numbers that did not align with the size of detention cells led to the phenomenon of overcrowding. In other words, such conditions could be deemed as torture against inmates. Despite Indonesia's ratification of the Convention Against Torture through Law Number 5 of 1998, torture in sentencing remained a major concern. The aim of this study was to examine the causes and impacts of overcrowding, analyze the phenomenon of overcrowding in Indonesian prisons and detention centers in accordance with the Convention Against Torture, and propose solutions to overcrowding as an implementation of the Convention Against Torture. The research employed a qualitative method with a normative legal approach to comprehend and interpret existing legal provisions and evaluate their implementation, thereby identifying the alignment between applicable law and its implementation. Primary data sources consisted of legislative regulations arranged according to the hierarchy of legal norms. Secondary legal materials included textbooks authored by eminent legal scholars, legal journals, academic opinions, legal cases, jurisprudence, and recent symposium outcomes relevant to the research topic. This study found that the Indonesian government endeavored to expand detention space to minimize torture and suffering that could occur in overcrowded cells, thereby facilitating the achievement of the goals of the Convention Against Torture.